Increasing the productivity of water in takein water-containing crystalline rocks by increasing their fracture by an explosion - В. М. Шестопалов; Л. І. Петренко; І. М. Романюк (Геофизический журнал, 2021)
Global warming, which has been observed in the world and Ukraine in particular in recent decades, may lead to a decrease in surface and groundwater. In addition, the high level of groundwater pollution and the policy of water purification is a matter of concern. Thus, the question of finding additional and alternative sources of drinking water today is highly urgent. A significant percentage of prospecting works of the last century was devoted to discovering the groundwater fields in fractured crystalline rocks of the Ukrainian Shield. As a rule, the productivity of wells of these formations did not have high flow rates, so even now, mostly the aquifers in sedimentary deposits have been exploited.